Inverse functions formula
in Other Math Topics by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Let y=f(x)=3^x, and take logs to base 3 of each side then log[3]y=x, or x=log[3]y. The inverse function is g so that x=g(y). Therefore the inverse function g(x)=log[3]x.

Example: g(81)=4 and f(4)=81.

by Top Rated User (645k points)

Related questions

1 answer
2 answers
0 answers
Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,917 questions
87,575 answers
4,217 users